Pengaruh Terapi Bicara Sederhana Terhadap Kemampuan Komunikasi Pasien Stroke Afasia Rumah Sakit X - Desy Anggrainingsih; Maria Susila Sumartiningsih (Borneo Nursing Journal (BNJ), 2026)
Stroke aphasia is a common language disorder in post-stroke patients and is characterized by difficulties in speaking, understanding, reading, and writing. Improving communication skills is an important focus in nursing practice to support the recovery of language function and quality of life of patients. This EBN aims to analyze nursing practices related to the effect of simple speech therapy on the communication skills of stroke aphasia patients at Hospital X. The EBN used a quasi-experimental design with a pretest–posttest control design. Respondents were divided into an intervention group that received simple speech therapy and a control group that received standard care. Communication skills were measured before and after the intervention using a verbal communication assessment scale. The results showed that the intervention group experienced a higher increase in communication skills (mean = 1.40; SD = 0.400) compared to the control group (mean = 1.03; SD = 0.106). An independent t-test showed a significant difference between the two groups (p-value = 0.004). These findings indicate that the implementation of simple speech therapy as part of nursing practice is effective in improving the communication skills of stroke aphasia patients. EBN emphasized the importance of integrating simple speech training-based interventions into rehabilitation programs to accelerate the recovery of patients' language function in health care facilities.